Post-Harvest Handling and Losses of Green Chilies: A Case Study from Bhutan - Changa Wangmo; Tashi Dendup (CV. Literasi Indonesia, 2021)
This study assessed post-harvest activities and post-harvest losses of green chili farming in Kabjisa, Punakha, Bhutan. Data came from interviewing 75 chili-growers selected via proportionate random sampling. Most farmers were found selling fresh chili (green chili). Few farmers produced blanched, dried, and powdered chilies for self-consumption. Most grown chili varieties were Wookup ema, Indian chili, and Yangtsep ema. Farmers mostly harvested chilies manually during the daytime in a bucket. The majority of the farmers have sorted and graded chilies based on disease infection, damaged parts, and size. Chilies are usually packed and stored for a night before the sale. Most chili losses occurred during harvesting, followed by marketing and sorting. The price of fresh chilies had to discount significantly during the peak season as farmers could not process chilies into other products. Hence, supporting farmers with dryer, cold storage, chili value addition infrastructure, and contract farming would minimize chili losses.